2020
DOI: 10.1038/s41598-020-70078-y
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D status, vitamin D intake, and skin cancer risk: a systematic review and dose–response meta-analysis of prospective studies

Abstract: Sun exposure is a major environmental risk factor for skin cancers and is also an important source of vitamin D. However, while experimental evidence suggests that vitamin D may have a protective effect on skin cancer risk, epidemiologic studies investigating the influence of 25-hydroxyvitamin D (25(OH)D) level and/or vitamin D intake on skin cancer risk are conflicting. A systematic review and dose-response meta-analyses of prospective studies was conducted to clarify these associations. Relevant studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 106 publications
(203 reference statements)
1
75
0
Order By: Relevance
“…Here ultraviolet B irradiation is a major risk factor and analysis of the relationship between serum calcidiol and melanoma is confounded by sun exposure. Importantly, no increased risk of melanoma occurred with vitamin D supplementation ( 130 ). Interestingly, several recent preclinical studies have suggested 7-dehydrocholesterol (a precursor of vitamin D) exerts anti-tumor activity in melanoma ( 131 ).…”
Section: Cancermentioning
confidence: 99%
“…Here ultraviolet B irradiation is a major risk factor and analysis of the relationship between serum calcidiol and melanoma is confounded by sun exposure. Importantly, no increased risk of melanoma occurred with vitamin D supplementation ( 130 ). Interestingly, several recent preclinical studies have suggested 7-dehydrocholesterol (a precursor of vitamin D) exerts anti-tumor activity in melanoma ( 131 ).…”
Section: Cancermentioning
confidence: 99%
“…Laboratory results of 25(OH)D were provided in nmol/L on a continuous scale. We categorized 25 Health survey and registry data. Baseline measurements of height (to the nearest 1 cm) and weight (to the nearest 0.5 kg) were obtained by trained staff according to a standardized protocol.…”
Section: Assessment Of Exposures Laboratory Analyses Concentrationsmentioning
confidence: 99%
“…Although laboratory studies provide a biological plausibility that an adequate level of 25(OH)D may inhibit cancer development, some recent studies have not found evidence of an association 20,21 , while others have reported an inverse association between 25(OH)D and cancer risk 22,23 . The three most recent meta-analyses of serum 25(OH)D and melanoma risk concluded that there is no association [24][25][26] . However, the two earlier Identification of cancer cases.…”
mentioning
confidence: 99%
“…Furthermore, 1,25(OH) 2 D3 has been shown to reduce postirradiation edema, inflammation, and photocarcinogenesis in mouse skin [ 11 ]. In a recent systematic review and dose–response meta-analysis of prospective studies regarding vitamin D intake and skin cancer risk [ 12 ], the authors reported that, while intakes of dietary or supplemental vitamin D were not associated with the risk of melanoma and squamous cell carcinoma, high intakes of vitamin D from diet and supplements were slightly associated with basal cell carcinoma risk. Considering that vitamin D levels are mainly affected by exposure to the sun, a higher risk of skin cancer may be confounded by sun exposure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review and dose–response meta-analysis of prospective studies regarding vitamin D intake and skin cancer risk [ 12 ], the authors reported that, while intakes of dietary or supplemental vitamin D were not associated with the risk of melanoma and squamous cell carcinoma, high intakes of vitamin D from diet and supplements were slightly associated with basal cell carcinoma risk. Considering that vitamin D levels are mainly affected by exposure to the sun, a higher risk of skin cancer may be confounded by sun exposure [ 12 ]. Other antioxidants, such as astaxanthin and other molecules, fail to demonstrate the capacity to reduce new melanoma or NMSC formation [ 1 , 3 ].…”
Section: Introductionmentioning
confidence: 99%